Optimizing fertilizer on oil palm production using the Goal Programming method / Fatimah Az-Zahra Azhar, Siti Hazlina Abdul Kudus and Nur Wahidah Zahari - Azhar, Fatimah Az-Zahra; Abdul Kudus, Siti Hazlina; Zahari, Nur Wahidah (2023)
In Malaysia, well-managed oil palm plantations spend the most on fertilizer management. Fertilizer purchases alone contribute to 85% or more of overall production costs. Fertilizer is any synthetic substance that is applied to soils. When growing plants, fertilizer enhances the supply of tissues and gives the plants more nutrients. This study proposes the Goal Programming approach to determine the accuracy rate of fertilizer used to produce a sustained maximum quality of oil palm fertility, to find the optimum mix of NPK fertilizer for oil palm plantation and to minimize the cost of production. The data was provided by interviewing the person in charge of the oil palm company in Kuala Pilah. The model was then run with LINGO 20.0 software. Nutri Gro, Power Gro, MPOB F1 and MPOB F5 fertilizers with various NPK concentrations were examined. To optimize oil palm production, 6.3 kg/ha of Nutri Gro, 1.575 kg/ha of Power Gro, 178.29 kg/ha of MPOB F1, and 162.26 kg/ha of MPOB F5 is required. This approach has been extensively utilized in various sectors to solve multi-criteria issues. This study is expected to be significant for both new and experienced farmers since it will help them make the most cost-effective decisions and guide them more about the benefits and consequences of fertilizer use in plants.